Infant and Young Child Feeding Practices in a Rural Area of North India - Satija, Mahesh; Sharma, Sarit; Chaudhary, Anurag; Kaushal, Pushapindra; Girdhar, Sangeeta (Asian Journal of Medical Sciences, 2015)
Background: Infant and young child feeding practices directly affect the nutritional status of children under two years of age and, ultimately, impact child survival. Therefore, the objective of this study was to assess the WHO infant and child feeding indicators in a rural area of Ludhiana, Punjab, India. Methods: A community based cross sectional study was conducted in fifteen villages of Ludhiana district under rural health training centre of Department of Community Medicine, Dayan and Medical College & Hospital, Ludhiana, Punjab. The data was obtained from mothers/primary caregivers of 813 living children 0-23 months of age group and information about seven core and three optional WHO infant and young child feeding indicators was collected using WHO questionnaire. Prevalence estimates with 95% confidence interval were calculated. A Χ2 test and Odds Ratio (OR) with 95% CI was calculated wherever required. Results: Only 56.7% of infants were put to breast within one hour of birth, while three fourths of infants younger than 6 months were exclusively breastfed. About seventy percent of children aged 12-15 months and 54.7% of children 20-23 months continued breastfeeding at 1 & 2 years respectively. Almost all the children born in the last 23 months were ever breastfed. Nearly ninety percent of infants 6-8 months of age were fed with complimentary foods at the recommended daily frequency. Conclusion: To improve breastfeeding practices, health education needs to be strengthened for target population having sub-optimal breastfeeding indicators. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12067 Asian Journal of Medical Sciences Vol.6(6) 2015 60-65